Smoked Catfish Processing Assessment (Mystus nemurus) with Liquid Smoke Using Dryer Heat Source Different Tools - Sony Wilson Giovani Silalahi; Syahrul '; Desmelati ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was intented to determine the effect of difference of using heat source dryer on the quality of Catfish (Mystus nemurus). The used method in this research was experimental, which using Complete Random Design (CRD). The treatment consists of three levels of treatment, namely M (solar source heat), L (Electrical energy source heat), and G (Gas energy source heat). drying time treatment is on three levels is 0 hours (T0), 3 hours (T1), 6 hours (T2), and 9 hours (T3). The used parameters are organoleptic value, water content, the value of fat content, protein content value and peroxide value. The results showed that the best treatment received L1 (Electrical energy source heat), with 10.29% average water content, 24.38% average fat content, 29.55 % average protein content, and also 2.91%. average peroxide.Keywords : Dryers, heat source, quality, Mystus nemurus, Drying